Bis[1-(3-cyanobenzyl)pyridinium] bis(1,2-dicyanoethene-1,2-dithiolato)nickelate(II) - Xian, Hua (International Union of Crystallography, 2010)
In the ionic title complex, (C(13)H(11)N(2))(2)[Ni(C(4)N(2)S(2))(2)], the Ni(II) ion is located on an inversion centre so the asymmetric unit contains one-half [Ni(mnt)(2)](2−) dianion (mnt(2−) is maleonitriledithiolate) and one 1-(3-cyanobenzyl)pyridinium cation ([CNBzPy](+)). The Ni(II) ion in the [Ni(mnt)(2)](2−) anion is coordinated by four S atoms of two mnt(2−) ligands, and exhibits square-planar coordination geometry. In the [CNBzPy](+) cation, the benzene and pyridine rings are twisted with respect to the C/C/N plane incorporating the methylene C atom that links them. The crystal structure is stabilized by Coulombic interactions.